2014
DOI: 10.1007/s13539-014-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Anamorelin HCl (ONO‐7643), a novel ghrelin receptor agonist, for the treatment of cancer anorexia‐cachexia syndrome: preclinical profile

Abstract: BackgroundAnamorelin HCl (ANAM) is a novel, orally active, ghrelin receptor agonist in clinical development for the treatment of cancer cachexia. We report in vitro and in vivo studies evaluating the preclinical pharmacologic profile of ANAM.MethodsFluorescent imaging plate reader and binding assays in HEK293 and baby hamster kidney cells determined the agonist and antagonist activity of ANAM, and its affinity for the ghrelin receptor. Rat pituitary cells were incubated with ANAM to evaluate its effect on grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 36 publications
(50 reference statements)
0
77
1
3
Order By: Relevance
“…Furthermore, it has better half life (7-12 h) compared to ghrelin (0.5 h) [69][70][71]. Though results of this drug are quite promising for cachexia treatment, further controlled studies with large sample size are still required to understand its efficacy and safety.…”
Section: Ghrelin and Its Receptor Agonistmentioning
confidence: 99%
“…Furthermore, it has better half life (7-12 h) compared to ghrelin (0.5 h) [69][70][71]. Though results of this drug are quite promising for cachexia treatment, further controlled studies with large sample size are still required to understand its efficacy and safety.…”
Section: Ghrelin and Its Receptor Agonistmentioning
confidence: 99%
“…Therapeutic effects included increases in lean mass as well as in fat mass (114) . Ghrelin receptor agonists such as anamorelin are currently also undergoing clinical testing and can achieve increases in body weight as well as appetite, but studies have so far focused on cancer cachexia, and large-scale studies are still missing (115)(116)(117)(118) . Besides, several myostatin antibodies are currently in development and are being tested in clinical trials.…”
Section: Cachexiamentioning
confidence: 99%
“…Ghrelin, a novel orexigenic gut hormone, is primarily secreted by the endocrine X/A-like cells of the stomach mucosa and also by intestinal mucosa, arcuate nucleus of the hypothalamus, pituitary gland, pancreatic islets, and other tissues (Khatib 2015b). Studies have shown that this 28-amino acid peptide hormone is an endogenous ligand for the growth hormone secretagogue receptor and can be a potential therapeutic agent for cachexia-associated cancer (Chen 2015;Garcia 2015;Pietra 2014;Tsubouchi 2014;Zhang 2015). It has shown promising results in randomised clinical trials (Garcia 2007;Garcia 2013;Garcia 2015;Khatib 2014b;Khatib 2014e;Madeddu 2015b).…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Ghrelin agonists are being developed and tested for the treatment of anorexia/cachexia. Anamorelin, a first-in-class, potent orallyactive and highly-specific ghrelin receptor agonist, increases food intake, body weight and lean body mass (Northrup 2013;Pietra 2014). It is well tolerated with no dose-limiting toxicities (Zhang 2015).…”
Section: Description Of the Interventionmentioning
confidence: 99%